Implementation of Risk Management with the ISO 31000 Approach in an Effort to Improve the Performance of Educational Services - Febiyanti, Herlina; Yuniar, Dwi Candra; Yiharodiyah, Lisa; Anwar, Syaiful (Graduate Program Magister Manajemen Pendidikan, 2024)
The implementation of a rapidly developing library service system can create threatening risks caused by the failure of library managers to assess the source of risk threats. Risks can take the form of events and conditions that result in disruption of information services and the decision-making process stops. The aim of this research is to describe the implementation of library service risk management at the Palembang Aviation Polytechnic Library using the ISO 31000 approach to determine the factors that influence the implementation of library risk management, especially in library material management activities. Library risk management at the Palembang Aviation Polytechnic Library has been implemented to anticipate various sources of risk threats by carrying out risk assessment, risk mitigation and risk evaluation activities through the Government Internal Control System (SPIP) in general.